The financial accountability framework of Australian public enterprise - McCrae Michael
This paper is concerned with the complexities of accountability for Australian public enterprise and analyses some of the conceptual issues which need to be addressed in developing a framework for reform. The analysis suggests that the matrix of financial accountability relationships is quite complex in terms of its objectives, its concern for both public interest and commercial viability issues and the number of participants. Furthermore, it operates in an intricate environment of political, administrative and control structures. Although the general financial reporting objectives for public and private enterprises may be similar from a conceptual view point, the assumptions underlying the private sector
Keywords: Public Sector; Public Enterprise; Finance; Accountability; Government Business Enterprises